Synthesis of TiO2 Nanotubes for Improving the Corrosion Resistance Performance of the Titanium Implants - Quan, Duong Hong; Tung, Nguyen Viet; Tuan, Ta Quoc; Tam, Le Thi; Phuong, Pham Thi Mai; Thang, Cao Xuan; Viet, Dao Xuan; Trung, Nguyen Kien; Huan, Pham Van; Ngoc, Nguyen Thi; An, Tran Trong; Vuong, Pham Hung (VNU Journal of Science: Mathematics - Physics; Vol 38 No 4, 2022)
TiO 2 nanotubes were successfully synthesized by electrochemical method. A fluoride salt mixture was used as an electrolyte for synthesizing TiO 2 nanotubes on titanium substrates. In this work, we have reported the synthesis procedure of TiO 2 nanotubes and investigated the corrosion resistance of TiO 2 nanotubes coated on the Ti substrate. FE-SEM was used to observe the morphology and determine the size of the TiO 2 nanotubes. The phase formation and crystal quality of TiO 2 nanotubes were studied by XRD measurements. One-microliter distilled water droplets were used to define the wettability of the TiO 2 nanotube surfaces by measuring the contact angle. The corrosion resistance behavior of specimens was analyzed in the simulated body fluid solution (SBF) using potentiodynamic polarization tests for potential application as implants.